Democratic and participatory approaches: Exemplars from early childhood education. (October 2014) - Luff, Paulette; Webster, Rebecca
The argument presented in this paper is that understanding and appreciating participatory approaches in early childhood education may serve as a basis for further development of such practices within the early years sector, and also provide examples and challenges for the leadership and management of schools and other educational institutions. Drawing upon John Dewey's ideal of education for democracy through communication and cooperation, we focus in turn on different stakeholders. Ideas and exemplars, from the literature and from research into practice, are selected to illustrate: respect for children's viewpoints; inclusion of student practitioners as legitimate participants; and possibilities for egalitarian approaches to decision making with staff through collegial, distributed leadership and management.